Molecular phylogenetic characterization of Collyriclum faba with reference to its three host-specific ecotypes - Heneberg, Petr; Literák, Ivan (Parasitology international, 2013)
Collyriclum faba (Bremser in Schmalz, 1831) is a monostome digenetic trematode with unknown life cycle. On its definitive bird host, C. faba occurs in pairs within a subcutaneous cyst, the location of which on the host body is the base for differentiating three ecotypes of C. faba. Here we examined the hypothesis connecting strong host-specificity of the ecotypes with the possible existence of cryptic speciation among C. faba. Analysis of conserved nuclear ribosomal DNA regions rejected the cryptic speciation hypothesis. Analyses of the variable ITS1 and ITS2 regions revealed that, despite some differentiation between the ecotypes, several large-scale indels occur in multiple ecotypes. Individuals from multiple cysts affecting each host individual differed in their ITS1 sequences, suggesting the individuals infecting a single host did not have common parents. Since we were the first to sequence C. faba, we attempted to verify its position in the current taxonomic system (Plagiorchiida: Gorgoderoidea). We found that C. faba segregates with the superfamily Microphalloidea (in order of maximum likelihood phylogeny: Prosthogonimidae, Pleurogenidae and Microphallidae) instead of any species of the superfamily Gorgoderoidea, as proposed in the past. The results necessitate reclassification of the family Collyriclidae as a member of Microphalloidea.
Keywords: DNA helmintů; druhová specificita; sekvence nukleotidů; DNA, Helminth; Male; Host-Parasite Interactions; tandemové repetitivní sekvence; genetická variace; fylogeneze; interakce hostitele a parazita; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; molekulární sekvence - údaje; infekce červy třídy Trematoda; mužské pohlaví; sekvenční seřazení; mezerníky ribozomální DNA; Species Specificity; nemoci ptáků; hostitelská specificita; Animals; Tandem Repeat Sequences; zvířata; Trematoda; Bird Diseases; Ecotype; Passeriformes; DNA, Ribosomal Spacer; Molecular Sequence Data; Base Sequence; Trematode Infections; Genetic Variation; ekotyp; Host Specificity; Sequence Alignment